JASA TITIPAN DALAM TRANSAKSI JUAL BELI ONLINE PERSPEKTIF HUKUM EKONOMI SYARIAH - Ayu Anggraini, Viedya Anantasya; Syai'in; Ahmad Faruq (Program Studi Hukum Ekonomi Syariah, Universitas Hasyim Asy'ari, 2023)
Jastip or personal shopper, offers a “buy goods” system. This service for purchasing goods by using social media as a place for transactions or using the Electronic-Commerce (e-commerce) system. In this muamalah activity, there are several rules in the form of conditions and pillars so that the implementation is carried out legally, in accordance with Islamic law. The problem in this study is that the sale and purchase contract does not comply with the rules, especially when it is implemented online, so it must comply with the provisions of sharia economic law. This research is a type of normative juridical research, namely legal research on library materials based on secondary data. Primary data includes Instargam accounts as objects of research as well as several books which are used as the main references, as well as supplemented by secondary data from articles and books on similar discussions. Data is collected through review and classifying the parts relevant to the discussion from books, documents and legislation. The data collected is then analyzed inductively into an easy-to-understand description, so that conclusions can be drawn on the problems based on the data found. In this study it was concluded that, deposit services in online buying and selling transactions are modern businesses that are in great demand by people. Because with a very simple transaction service system, orders are in accordance with the instructions that have been uploaded on the Instagram account of the entrusted service provider, the owner or owner writes a description of the product along with the price, then the customer/buyer can order directly via WhatsApp or DM. This JMS deposit service provider account usually uses the payment method by cash transfer and COD or paying on the spot when the goods arrive in the hands of the customer. Meanwhile, JTBJ, JBS and NP accounts use the mandatory transfer payment method. And for the senders of these 4 accounts using the meeting method at an agreed place and using an expedition attorney. Related to the perspective of sharia economic law regarding safekeeping services in online buying and selling, online buying and selling transactions are permitted in sharia economic law because in carrying out these entrusted service transactions using a sale and purchase contract. The sale and purchase transaction contract for this deposit service for all accounts uses a wakalah bil ujrah contract, namely an agreement between the personal shopper and the customer, while the usual sale contract is for the personal shopper and the outlet. So there are 2 contracts in this deposit service transaction. Keywords: safekeeping services, online transactions, online buying and selling, sharia economic law.